2012
DOI: 10.1158/0008-5472.can-11-3004
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Causes Epithelial–Mesenchymal Transition in the Prostate: Implications for Androgen-Deprivation Therapy

Abstract: Androgen deprivation is currently a standard-of-care, first-line therapy for prostate cancer in the United States. Although this regimen effectively regresses androgen-dependent disease, relapse often occurs in an androgenindependent manner and is associated with poor prognosis. Such castration-resistant prostate cancer represents a major clinical challenge, and the mechanisms underlying castration resistance are not fully understood. Epithelial-mesenchymal transition (EMT) is a key developmental process and h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
315
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(337 citation statements)
references
References 39 publications
21
315
0
Order By: Relevance
“…As well, TGF-b1 expression was also shown to be induced by androgen deprivation in human prostatic tissues (Fuzio et al 2012). We and others have shown that the EMT-regulating transcription factor Twist1 was induced by androgen deprivation (Shiota et al 2012b, Sun et al 2012. Furthermore, CRPC tumors from LNCaP-xenograft model using castrated mice showed augmented AR signaling as well as an EMT phenotype, characterized by increased expression of Twist1 as well as other mesenchymal markers.…”
Section: Discussionmentioning
confidence: 82%
“…As well, TGF-b1 expression was also shown to be induced by androgen deprivation in human prostatic tissues (Fuzio et al 2012). We and others have shown that the EMT-regulating transcription factor Twist1 was induced by androgen deprivation (Shiota et al 2012b, Sun et al 2012. Furthermore, CRPC tumors from LNCaP-xenograft model using castrated mice showed augmented AR signaling as well as an EMT phenotype, characterized by increased expression of Twist1 as well as other mesenchymal markers.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, targeting these transcription factors might provide an effective way to contrast the expansion of the highly tumorigenic stem-like tumor cells in advanced prostate cancer. CSCs are intrinsically resistant to androgen deprivation therapy and many cytotoxic drugs causing treatment failures and disease recurrence (8)(9)(10)49). CSC-targeted agents could be most effective in combination with current therapies to increase response rates and prolong survival in advanced prostate cancer patients (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the transcription factor ZEB1 may be induced by dihydrotestosterone and is mediated by two androgen-response elements (40). Recently, Sun and colleagues showed that androgen deprivation causes EMT in animal models and in tumor samples of patients treated with hormone therapy (41). Moreover, the presence of AR-truncated isoforms, which are increased in the castration-resistant progression, regulate the expression of EMT (42).…”
Section: Discussionmentioning
confidence: 99%